(untitled) (Stato, Chiese e pluralismo confessionale, 2020)
SOMMARIO: 1. Introduzione - 2. Premessa teorica: la funzione di orientamento sociale del diritto - 2.1. Chiarezza dei messaggi normativi (a monte) - 2.2. Chiarezza dei messaggi normativi (a valle) - 3. Accomodamenti ragionevoli nel diritto antidiscriminatorio dell’Unione europea - 3.1. Perché manca una disposizione sugli accomodamenti ragionevoli basati su tutti i fattori? - 3.2. Perché ampliare la norma sugli accomodamenti ragionevoli? - 4. Dalla norma inderogabile al diversity management - 5. Ripensare il diritto antidiscriminatorio e il diversity management in una prospettiva interculturale - 6. Considerazioni conclusive. Reasonable Accommodation Based on Religion in Law and Diversity Management ABSTRACT: The ban on discrimination against workers grounded on religion is a fundamental principle enshrined in the European Union’s primary legislation and anti-discrimination law. However, currently, there is no binding provision at this level of legislation which imposes on employers to adopt reasonable accommodation based on this category. Many scholars promote the adoption of this measure based on religion. Still, the recent jurisprudence of the Court of Justice does not seem encouraging in this sense. In light of this situation, the article aims to investigate the reasons underlying the limitations of the hard law provisions and the implications of the shift from the level of the mandatory norm to that of policy and diversity management in accommodating religious diversity at work, with particular regard to Muslim women working in the private sector. European institutions seem to delegate the law-related function of social orientation to policy and diversity management. Various critical issues emerge from this process of de-juridification, although diversity management generates some good practices, also within the so-called Diversity Charters. With the aim to support the implementation of reasonable religion-based accommodation, this article suggests rethinking the anti-discrimination law and diversity management from an intercultural perspective.